Feline Infectious Peritonitis in British Short Hair Cat at Petvet Animal Clinic Jakarta - Muhamad Irfan Hartono; Endang Endrakasih; Harry Harry (Universitas Airlangga, 2022)
Background: Feline Infectious Peritonitis (FIP) is a disease caused by Feline Corona Virus (FCoV) which can cause acute respiratory disorders or enteritis in cats. Purpose: studying FIP and the treatment that must be given to patients who are positive for FIP. Case Analysis: This case was found at the Petvet Animal Clinic Jakarta in a British Short Hair Cat. Examination and treatment will be carried out on May 22, 2021 – June 3, 2021. The examination method is carried out by clinical examination and laboratory examination. Clinical examination was carried out by inspection and palpation methods. Laboratory examinations were carried out by examining the FCoV Rapid test, blood examination, abdominocentesis, abdominal fluid examination and polymerase chain reaction. Based on the results of the clinical examination, FCoV rapid test, hematology and Rivalta testing, it can be concluded that the FIP case in cat at the Petvet Animal Clinic belongs to the wet type (effusive) FIP. Conclusion: It is necessary to carry out other supporting diagnoses such as ELISA (Enzyme-Linked Immunosorbent Assay) and PCR (Polymerase Chain Reaction) testing. There is no cure for this FIP case, but symptomatic and supportive therapy is very helpful to reduce clinical symptoms and increase body endurance.